Prevalence and factors associated with probable obstructive sleep apnea among patients with hypertension in two primary care clinics in Miri, Sarawak, Malaysia - Ching, Siew Mooi *; Rajvinder, Singh; Fatimah, Shahidah Binti Azmi; Chong, Khian Lu; Ong, Cynthia Ruey Shyuan; Nur Afiqah, binti Ayob; Patil, Mansi; Lee, Kai Wei; Vasudevan, Ramachandran; Arora, Viresh (Springer, 2024)
Purpose: Obstructive sleep apnea (OSA) has been increasingly recognized as an important factor contributing to medical morbidity and mortality. It was reported that more than half of the population with hypertension had OSA. Limited studies have been done on assessing OSA in hypertensive patients. This study aimed to determine the prevalence, socio-demographic characteristics, and factors associated with probable OSA in hypertensive patients in primary care clinics in Sarawak.